Changes in Physiological Parameters, Lipid Metabolism, and Expression of MicroRNAs in Genetically Improved Farmed Tilapia (Oreochromis niloticus) With Fatty Liver Induced by a High-Fat Diet - Tao, Yi-Fan; Qiang, Jun; Bao, Jing-Wen; Chen, De-Ju; Yin, Guo-Jun; Xu, Pao; Zhu, Hao-Jun (Frontiers in Physiology, 2018)
Tilapia is susceptible to hepatic steatosis when grown in intensive farming systems. The aim of this study was to explore the mechanism of fatty liver induced by a high-fat diet (HFD) in genetically improved farmed tilapia (GIFT, Oreochromis niloticus). Juvenile GIFT were fed with HFD or a normal-fat diet (NFD) for 60 days. Substantial fat deposition in the liver of HFD-fed GIFT on days 20, 40, and 60 was observed using hematoxylin – eosin staining and oil red O staining. The increased fat deposition was consistent with increased triglyceride (TG) and total cholesterol (TC) levels in the liver of HFD-fed GIFT. There were significant differences (P < 0.05) in serum biochemical indexes (TG, TC, low density lipoprotein-cholesterol, and insulin contents, and alanine aminotransferase activity) between GIFT fed a HFD and GIFT fed a NFD on days 20, 40, and 60. Furthermore, 60 days of a HFD significantly changed (P < 0.05) the hepatic fatty acid composition, and led to increased polyunsaturated fatty acid levels and decreased saturated fatty acid and monounsaturated fatty acid levels. Hepatic antioxidant enzyme activities increased by day 20 and then declined, which led to an increase in malondialdehyde contents in the liver of HFD-fed GIFT. Molecular analyses revealed that the microRNAs miR-122, miR-29a, and miR-145-5p were upregulated, whereas miR-34a was downregulated in HFD-fed GIFT. SCD, ELOVL6, and SRD5A2 encode three important enzymes in lipid metabolism, and were identified as potential targets of miRNAs. The transcript levels of hepatic SCD and ELOVL6 were decreased and that of hepatic SRD5A2 was increased in GIFT fed a HFD. Overall, the results of this study revealed a potential link between miRNAs and fatty liver induced by HFD, and suggest that a HFD could lead to excess fat deposition in the GIFT liver, which may disrupt hepatic lipid metabolism and reduce the antioxidant defense capacity.